2018
DOI: 10.1080/10409289.2018.1487222
|View full text |Cite
|
Sign up to set email alerts
|

What Happens During Language and Literacy Coaching? Coaches’ Reports of Their Interactions With Educators

Abstract: Research Findings: This study investigated coaches' interactions with educators in the context of a large-scale, state-implemented literacy professional development (PD). We examined log data and open-comment reports to understand what coaches found salient about their interactions with educators as well as how those reports aligned with the initial design of the PD. Coaches reported spending a large proportion of their interactions with educators completing administrative tasks. Our findings also indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…A yearlong study, in which we investigated how five SLPs serving in coaching roles built teacher capacity in the area of classroom literacy instruction through one‐to‐one coaching conversations with teachers, revealed that only one of the coaches, highlighted in a separate case study (Pletcher, Hudson, & Watson, 2019), consistently employed a variety of questioning techniques to promote inquiry in her conversations with teachers. Moreover, detailed analyses of coaching conversation transcripts from the other SLPs suggested that providing examples and solving problems for teachers may come more naturally than the use of questioning to probe reflection, a finding that mirrors those of Schachter et al (2018).…”
Section: “So What I Would Do Is…”mentioning
confidence: 60%
See 1 more Smart Citation
“…A yearlong study, in which we investigated how five SLPs serving in coaching roles built teacher capacity in the area of classroom literacy instruction through one‐to‐one coaching conversations with teachers, revealed that only one of the coaches, highlighted in a separate case study (Pletcher, Hudson, & Watson, 2019), consistently employed a variety of questioning techniques to promote inquiry in her conversations with teachers. Moreover, detailed analyses of coaching conversation transcripts from the other SLPs suggested that providing examples and solving problems for teachers may come more naturally than the use of questioning to probe reflection, a finding that mirrors those of Schachter et al (2018).…”
Section: “So What I Would Do Is…”mentioning
confidence: 60%
“…This may result because many SLPs receive little to no training prior to assuming their role (Toll, 2018). A lack of training in coaching strategies consequently may lead SLPs to believe that directly providing teachers with resources and information will be sufficient in moving them toward a change in their literacy practices (Mangin & Dunsmore, 2013; Schachter, Weber‐Mayrer, Piasta, & O’Connell, 2018).…”
mentioning
confidence: 99%
“…Observation has been reported by coaches as one of the most commonly used strategies in literacy-related intervention/instruction coaching (Schachter et al, 2018).…”
Section: Coaching To Improve Intervention Fidelitymentioning
confidence: 99%
“…The data collected from observation helps the coach to build a better understanding of not only the interventionist's skill level but also the contextual factors (e.g., distractions in the environment or student behavioral issues) during the intervention session. Observation has been reported by coaches as one of the most commonly used strategies in literacy‐related intervention/instruction coaching (Schachter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Instructional strategies support professional learning by offering teachers detailed procedures for enacting student learning (Kennedy, 2016). Research shows that coaches modeling effective practice is a powerful strategy to support teacher change (Darling-Hammond et al, 2017; Schachter et al, 2018). For a virtual coach, modeling is a bit different than face-to-face coaching.…”
Section: Vector In Practicementioning
confidence: 99%